USING INTERACTIVE METHODS IN TEACHING THE UZBEK LANGUAGE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
One of the main tasks of teaching the Uzbek language is to form a person who has an independent mind and can consciously and actively participate in social and political life. The maturation of such a future generation will speed up the wide implementation of the foundations of democracy in the life of the country and the process of building a legal, developed state.